Quantal analysis of synaptic plasticity in the rat hippocampus - Hannay, R; Hannay, Robert Timo (1994)
Long-term potentiation (LTP) is a long-lasting increase in efficacy shown by some synapses in the brain and elsewhere that might be involved in certain types of learning and memory. It has been most intensively studied in the hippocampus, a brain area known to be important in memory. LTP induction is triggered by a rise in calcium concentration inside the postsynaptic cell. Whether LTP is expressed presynaptically or postsynaptically is less clear, with results from different laboratories appearing to contradict one another. Quantal analysis is one approach to this question. Neurotransmitter is released from the presynaptic cell in discrete packets of roughly equal size, known as quanta. If the increased response recorded during LTP is composed of a greater number of quanta, it would suggest a presynaptic change. On the other hand, an increase in the postsynaptic effect produced by each quantum would suggest that there had been a change in the postsynaptic cell. I made intracellular voltage recordings of small excitatory postsynaptic potentials (EPSPs) from pyramidal neurones in area CA1 of rat hippocampal slices. I induced LTP and determined the site of the change using three quantal analysis procedures: 1/CV² graphs, amplitude frequency histograms and 'constant N analysis'. The results indicate that EPSPs can show both presynaptic and postsynaptic changes. However, the proportions varied considerably between individual EPSPs and seemed to depend on the initial 'setting' of the synapse. This, in turn, can depend on the experimental conditions, which might explain at least some of the contradictions in earlier results. I also carried out a similar study of a briefer form of enhancement known as shortterm potentiation (STP). I found that this too is caused by both presynaptic and postsynaptic changes and that their proportions seem to obey a similar rule to LTP. This suggests that LTP and STP are not separate phenomena, as some have suggested, but are closely related. I attempted a similar study of mossy fibre inputs to pyramidal cells in area CA3 of hippocampal slices. However, it was difficult to obtain uncontaminated mossy fibre responses, so the results of this study are preliminary.